Adversity Quotient: The Role of Social Support and Optimism as Mediator Variables in Working Students - Safitri, Novia Rahmani; Mora, Linda; Mustika, Haryanti (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
A major challenge for working students is balancing the demands of study and work simultaneously. The ability to face challenges and overcome obstacles, known as adversity quotient, is very important for working students. The purpose of this study is to analyze how social support affects the adversity quotient of working students, with optimism having a role in the mediator variable. This study adopted a quantitative approach by involving 225 students from UBP Karawang Psychology Department as participants. The sampling technique applied was non-probability sampling using purposive sampling approach. Data collection was conducted through three instruments, namely the Adversity Response Profile (ARP), Life Orientation Test - Revised (LOT-R), and the Multidimensional Scale of Perceived Social Support (MSPSS). Data were analyzed by testing the assumptions of normality and linearity, followed by path analysis. The results indicated that social support and adversity quotient did not show a significant influence (p > 0.067). However, there was a significant influence between social support and optimism (p < 0.001). In addition, optimism also showed a significant influence on adversity quotient (p < 0.001). Significantly (p < 0.001) revealed optimism plays a role as a full mediator of social support on adversity quotient.Tantangan besar bagi mahasiswa bekerja merupakan menyeimbangkan tuntutan perkuliahan dan pekerjaan secara bersamaan. Kemampuan untuk menghadapi tantangan dan mengatasi hambatan, yang dikenal sebagai adversity quotient, sangat penting bagi mahasiswa bekerja. Tujuan penelitian ini untuk menganalisis bagaimana dukungan sosial mempengaruhi adversity quotient mahasiswa bekerja, dengan optimisme yang memiliki peran dalam variabel mediator. Penelitian ini mengadopsi pendekatan kuantitatif dengan melibatkan 225 mahasiswa dari Jurusan Psikologi UBP Karawang sebagai partisipan. Teknik pengambilan sampel yang diterapkan adalah non-probability sampling menggunakan pendekatan purposive sampling. Pengumpulan data dilakukan melalui tiga instrumen, yakni Adversity Response Profile (ARP), Life Orientation Test – Revised (LOT-R), serta Multidimensional Scale of Perceived Social Support (MSPSS). Data dianalisis dengan menguji asumsi normalitas dan linearitas, dilanjutkan dengan analisis jalur (path analysis). Hasil penelitian mengindikasikan bahwa dukungan sosial dan adversity quotient tidak menunjukkan pengaruh yang signifikan (p > 0.067). Namun demikian, ditemukan adanya pengaruh yang signifikan antara dukungan sosial dan optimisme (p < 0.001). Selain itu, optimisme juga menunjukkan pengaruh signifikan terhadap adversity quotient (p < 0.001). Secara signifikansi (p < 0.001) mengungkapkan optimisme berperan sebagai mediator penuh dukungan sosial terhadap adversity quotient.